Magnetic Field Stimulation Effect on Germination and Antioxidant Activities of Presown Hybrid Seeds of Sunflower and Its Seedlings - Shazia Anwer Bukhari; Muhammad Tanveer; Ghulam Mustafa; Nighat Zia-Ud-Den (Journal of Food Quality)
Magnetic field biostimulation plays a significant role in enhancing the germination of seeds and increasing the metabolic rate. The low magnetic field effect for long exposure time and its effect on antioxidant profiling have not been studied. Therefore, in the recent findings, the static magnetic field’s impact on sunflower seeds subjected to the magnetic field at varying intensity (millitesla) for different exposure times was examined. The effectiveness of magnetic biostimulation on presown sunflower seeds, growth parameters of seedlings (biomass, root and shoot length, fresh and dry weight of roots, shoots, leaf, and height of plants), and antioxidant activities were also studied. It has been revealed that magnetic treatment at 50 mT/45 min greatly influenced the growth parameters, including mean germination growth (100 ± 0.02) and final emergence rate. Concerning the antioxidant parameters, seed variety FH620 at 500 µg/µL concentration showed significant results compared to other varieties. FTIR was employed to determine the conformational changes and functional groups of organic compounds from sunflower seedlings. Tocopherol analysis by HPLC showed that magnetic treatment at 50 mT/45 min had a higher concentration of vitamin E compared to the control group. These modifications indicated that magnetic field induction enhanced seeds’ inner energy that led to seedlings’ growth and development enhancement. Besides, magnetic field pretreatment has been shown to have a beneficial influence on sunflower seeds and their bioactive compounds. Future studies should be focused on growth characteristics at the field level and yield attributes.